The Correlation between Self-esteem and Reading Comprehension Achievement of the Eleventh Grade Students of SMA NEGERI 5 Palembang - Maya Anjela; Eryansyah Eryansyah; Lingga Agustina Suganda (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2020)
The objectives of this study were (1) to find out if there was a significant correlation between students’ self-esteem and their reading comprehension achievement, and (2) to find out whether or not there was a significant contribution of self-esteem to the achievement of students’ reading comprehension. The sample of this study was 118eleventh-grade students of SMA Negeri 5 Palembang. The sampling technique used was purposive sampling. In collecting the data, the researcher used two kinds of instruments, a self-esteem questionnaire and reading comprehension tests in a form of multiple-choice questions. The Pearson Product Moment Correlation Coefficient and Simple Linear Regression in SPSS version 21 were used to analyze the data. The result of Pearson Product Moment Correlation Coefficient showed that (1) there was a significant correlation between self-esteem and students’ reading comprehension achievement because p-value (0.000) was higher than (0.05), and (2) there was 47% contribution of self-esteem to students’ reading comprehension achievement.